2020
DOI: 10.1002/nop2.702
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of metacognitive ability, self‐directed learning ability and critical thinking in nursing students: A cross‐sectional study

Abstract: Aim To understand the status quo of metacognitive ability (MA), Self‐directed learning (SDL) ability and critical thinking (CT) ability of five‐year higher vocational nursing students as well as the correlation among them. Background MA, SDL ability and CT are the core abilities that nursing students must have and they are the important factors to improve students’ nursing service quality and lifelong learning ability. Design A quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 35 publications
4
19
0
1
Order By: Relevance
“…Metacognition is defined as the knowledge and control of learning strategies by perceiving to what degree individuals are aware of these learning strategies, how they understand them to work, and how they know when to use them [6,7]. Metacognition has been found to facilitate students' learning performance and the development of their generic capabilities [8][9][10][11]. Various studies have demonstrated that university students with a higher level of metacognitive awareness have better decision-making skills [6] and achieve better academic performance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Metacognition is defined as the knowledge and control of learning strategies by perceiving to what degree individuals are aware of these learning strategies, how they understand them to work, and how they know when to use them [6,7]. Metacognition has been found to facilitate students' learning performance and the development of their generic capabilities [8][9][10][11]. Various studies have demonstrated that university students with a higher level of metacognitive awareness have better decision-making skills [6] and achieve better academic performance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Black et al (2016) confirms that metacognitive ability can be taught and people can be trained to get the required techniques. One needs to be aware of his metacognitive ability, for this leads to self-directed learning readiness (Jin & Ji, 2020;Ors &Titrek, 2018). Metacognitive ability is a good predictor of leadership development (Mango et al, 2019).…”
Section: Developmental Readinessmentioning
confidence: 99%
“…3 Given the responsibilities and scope of nursing practice and the need for correct decision-making in the nursing care process, nurses must acquire the ability to analyze critical clinical situations and make life-saving decisions in complex circumstances. 4 The most important benefits of correct and timely decision-making in nursing include speeding up patients' treatment process, providing higher levels of patient care, reducing treatment costs, facilitating the proper use of health workforce and medical equipment, and improving the quality of care. 5 On the other hand, the lack of timely and correct decision-making in nursing endangers public health.…”
Section: Introductionmentioning
confidence: 99%